2000
DOI: 10.1117/12.395703
|View full text |Cite
|
Sign up to set email alerts
|

<title>Electrostatic discharge/electrical overstress susceptibility in MEMS: a new failure mode</title>

Abstract: Electrostatic discharge (ESD) and electrical overstress (EOS) damage of Micro-Electro-MechanicalSystems (MEMS) Fig. 1 [4].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…In practical applications, micro-electromechanical systems (MEMSs), like micromachines and micro-mirror arrays, function by electrostatic actuation [2,3], while the electronic devices, like photomasks [4,5] and magnetoresistive (MR), giant magnetoresistive (GMR), and tunneling magnetoresistive (TMR) devices used in the magnetic recording industry [6][7][8], are at risk of accumulating static charges and the consequent threats of electrostatic discharge (ESD); both the microdevices and microstructures are associated with a strong electric field strength within microgaps [9]. For instance, the high operating voltages required for RF MEMS switches [10][11][12][13], micro-motors [14,15] and micro-mirror [16,17] can create sparking or breakdown across microgap structures due to electrical overstress (EOS) that may damage or destroy sensitive equipment, especially when the devices are subjected to a complex electromagnetic environment [7,18].…”
Section: Background and Motivationmentioning
confidence: 99%
“…In practical applications, micro-electromechanical systems (MEMSs), like micromachines and micro-mirror arrays, function by electrostatic actuation [2,3], while the electronic devices, like photomasks [4,5] and magnetoresistive (MR), giant magnetoresistive (GMR), and tunneling magnetoresistive (TMR) devices used in the magnetic recording industry [6][7][8], are at risk of accumulating static charges and the consequent threats of electrostatic discharge (ESD); both the microdevices and microstructures are associated with a strong electric field strength within microgaps [9]. For instance, the high operating voltages required for RF MEMS switches [10][11][12][13], micro-motors [14,15] and micro-mirror [16,17] can create sparking or breakdown across microgap structures due to electrical overstress (EOS) that may damage or destroy sensitive equipment, especially when the devices are subjected to a complex electromagnetic environment [7,18].…”
Section: Background and Motivationmentioning
confidence: 99%
“…Emerging technologies such as microelectromechanical systems (MEMS) and nanoelectromechanical systems (NEMS) which include microgap and nanogap assemblies [4]will inherently be extremely sensitive to ESD. Since ESD is effectively a charge injection source, it is to be seriously considered as a major reliability issue in MEMS [5,6]. Parasitic charging of the dielectrics in MEMS devices including microphones and switches results in undesired electrostatic forces on these actuators; studies have shown that this is a serious performance issue [7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Electrostatic discharge (ESD) is an important consideration and has been observed as a failure mode in MEMS [26], [27]. A static charge of several thousand volts can easily build up on a MEMS part as it is unloaded from a plastic tray, or handled by an operator who has not taken suitable precautions to ground himself.…”
Section: Effect Of Electrode Gap and Packaging Gas On Breakdown Vmentioning
confidence: 99%